« Hybrids of autobiography and argument » - Elisa Russian (Contextes, 2025)
British narratives of class transition are closely linked to the emergence of cultural studies and the growing emphasis on the notion of lived experience in postwar literary and political debates. These texts often combine autobiography and social theory to examine class relations. Landscape for a Good Woman (1986), by historian Carolyn Steedman, is a paradigmatic example of this tradition. Drawing on the form of the case study, Steedman places affects at the center of experiences of social mobility and foregrounds trajectories that have remained on the margins of dominant critical frameworks. A similar approach characterizes Respectable (2016), by journalist Lynsey Hanley, who, in a neoliberal context, analyzes how geographical and social spaces are structured by deeply internalized mechanisms of separation. Through the narration of lived experiences, Steedman and Hanley thus develop a critique of the power relations that shape social mobility at the intersection of class and gender.